Association between lactate dehydrogenase to albumin ratio and ICU mortality in patients with acute kidney injury: a retrospective cohort study - Gao, Jianting; Chen, Huizhen; Wu, Yiyi; Xu, Chang; Jin, Yan (Frontiers in Nephrology, 2025)
BackgroundAcute kidney injury (AKI) is a prevalent and severe medical condition that is frequently observed in the intensive care unit (ICU). Although numerous biomarkers have been identified to predict the prognosis of AKI, the lactate dehydrogenase to albumin ratio [LDH/ALB ratio (LAR)] has not been extensively investigated. The principal objective of this study was to assess the relationship between LAR and all-cause mortality in patients with AKI.MethodsA total of 6,831 AKI patients were included in this study, divided into survival (n = 5,152) and non-survival groups (n = 1,679). The association between LAR and mortality was examined through restricted cubic spline (RCS) analysis and Cox regression analysis. Subgroup analysis was used to search for interactive factors. Additionally, the prognostic capability of LAR was further evaluated using receiver operating characteristic (ROC) curve analysis.ResultsThe LAR was remarkably higher in the non-survival group (p < 0.001). RCS indicated a non-linear correlation between LAR and ICU death (p for non-linearity < 0.001). A LAR of 10.4 was used as the cutoff point to generate the high-LAR and low-LAR subgroups, and the Kaplan–Meier curves revealed that the ICU cumulative survival rate for patients with AKI was significantly lower in the high-LAR group (log-rank p < 0.001). The LAR’s prediction of ICU mortality in AKI patients yielded an area under the ROC curve of 0.65.ConclusionOur research suggests that LAR monitoring may be promising as a prognostic marker among patients with AKI. Higher LAR is associated with greater ICU mortality.